Development and testing of the eye-pointing classification scale for children with cerebral palsy. Issue 8 (10th April 2022) - Clarke, Michael T.; Sargent, Jenefer; Cooper, Rosemary; Aberbach, Gabriella; McLaughlin, Laura; Panesar, Gurveen; Woghiren, Amie; Griffiths, Tom; Price, Katie; Rose, Caroline; Swettenham, John
Abstract: Purpose: The aim of this study was to develop and test a new classification scale to describe looking behaviours (gaze fixations and gaze shifts) in relation to eye-pointing. Methods: The Eye-pointing Classification Scale (EpCS) was developed and tested following established procedures for the construction and evaluation of equivalent scales, and involved 2 phases: Drawing on research literature, Phase 1 involved initial drafting of the scale through a series of multi-disciplinary group discussions; evaluation of the scale through a survey procedure, and subsequent expert group evaluation. Phase 2, was an examination of scale reliability and relationships between child characteristics and level of EpCS classification. Results: In Phase 1, an initial draft of the scale was developed and then evaluated by 52 participants in 10 countries, leading to its refinement. Subsequent expert evaluation of content, style and structure indicated that no further refinement was required. In Phase 2, the scale achieved excellent levels of reliability in clinical testing. A significant relationship was identified between level of child motor ability and EpCS classification, and level of child language understanding and EpCS classification. Implications for rehabilitation: Non-speaking children with severe bilateral cerebral palsy who have limited upper limb movement may communicate by using controlled looking behaviours to point to objects and people, referred to as eye-pointing. However, there is little consensus as to which looking behaviours represent eye-pointing and which do not. The Eye-pointing Classification Scale (EpCS) was developed to describe looking behaviours related to eye-pointing in this population of children The EpCS provides a new robust tool for clinical management and research with children with cerebral palsy.